Peningkatan Kompetensi Pembelajaran Praktikum Mahasiswa dengan Model Based Keyword Successs Learning - Fauzan Putraga Al Bahri; Syafrinal Syafrinal (Ideas Publishing, 2021)
One of the strategies used to present effective information is the strategy of using keyword-based learning based on the application of keywords in understanding learning material on the use of computers in order to improve students' memory in developing better ways to encode information so that it will be easier to remember. This study aims to develop a model and implement Model-Based Keyword Success Learning (BKSL) as a solution to improve practicum learning competencies in the new normal era so that its application can be more effective and efficient, as well as facilitate the presentation of teaching materials more easily understood by students. This method involves media and techniques consisting of games; debate; discussion; story; film; conversation; and vocabulary. The approach used in this research is a qualitative approach with a descriptive method. The stages of data collection include a) interviews; b) observation; and c) documentation, the technique of drawing conclusions by analyzing documents, whether written, pictures, or electronically, while the data analysis technique goes through the following stages: a) data reduction; b) data presentation; and c) drawing conclusions. This learning involves several assessment variables in taking the results of the assessment consisting of, namely; games, debates, discussions, stories, films, conversations, and vocabulary that are carried out practice directly to students, the results of this study note that the most popular learning media are using games, films, and vocabulary. While learning with debate, conversation, story, and discussion models is not much liked. Salah satu strategi yang digunakan untuk menyajikan informasi efektif adalah strategi penggunaan keyword based learning berbasis penerapan kata kunci dalam memahami materi belajar pada penggunaan komputer agar meningkatkan memori siswa dalam mengembangkan cara yang lebih baik untuk menyandikan informasi sehingga akan lebih mudah diingat. Penelitian ini bertujuan untuk mengembangkan model dan mengimplemetasi Model Based Keyword Successs Learning (BKSL) sebagai solusi peningkatan kompetensi pembelajaran praktikum di era new normal, sehingga penerapannya dapat lebih efektif dan efesien, serta memudahkan penyajian materi bahan ajar secara lebih mudah dipahami oleh mahasiswa. Dalam metode ini melibatkan media dan teknik yang terdiri dari game, debat, diskusi, cerita, film, percakapan, dan kosa-kata. Pendekatan yang digunakan pada penelitian ini adalah pendekatan kualitatif dengan metode deskriptif. Tahapan pengumpulan data meliputi: a) wawancara; b) observasi; dan c) dokumentasi, teknik pengambilan kesimpulan dengan cara untuk menganalisis dokumen baik tertulis, gambar, maupun elektronik, sedangkan pada teknik analisis data melalui tahapan: a) reduksi data; b) penyajian data; dan c) penarikan kesimpulan. Pembelajaran ini melibatkan beberapa variabel penilaian dalam pengambil hasil penilaian terdiri dari yaitu; game, debat, diskusi, cerita, film, percakapan, dan kosakata yang dilakukan secara praktik langsung ke mahasiswa. Hasil penelitian ini diketahui bahwa media pembelajaran yang paling diminati adalah dengan menggunakan game, film, dan kosa-kata. Sedangkan pembelajaran dengan model debat, percakapan, cerita, dan diskusi tidak banyak disukai.